Optimization Of Flame Retardant Composite Parameters Based On Oil Palm Trunk Using Response Surface Methodology And Its Suitability For Other Biomass - Yusof, Madihan (2024)
The flame retardant composite discussed in the study was developed by treating oil palm trunk (OPT) with a sodium chloride (NaCl) solution and then bonding it with poly(vinyl) alcohol (PVOH) and calcium carbonate (CaCO3) as a filler. The experimental design utilized central composites design (CCD) within the response surface methodology (RSM) framework to optimize the combination of NaCl, PVOH, and CaCO3 in the OPT composites. The range of combinations for NaCl, PVOH, and CaCO3 varied from 10% to 30%, 10% to 20%, and 4% to 10%, respectively. Optimization criteria were based on their effects on bending strength (MOR), internal bonding (IB), and limited oxygen index (LOI). Through analysis, the optimal ratio for producing flame retardant composite boards from OPT was determined to be NaCl 10%, PVOH 20%, and CaCO3 4%. Predicted values from the empirical model for MOR, IB, and LOI were 12.96 MPa, 4.19 MPa, and 33.73%, respectively. Experimental results closely aligned with these predictions, with MOR at 11.13 MPa, IB at 5.78 MPa, and LOI at 32.3%. The study also investigated the application of this optimal ratio to rubberwood particles, comparing the resulting flame retardant composite board with that of OPT. Various analyses such as Fourier Transform Infrared (FTIR), X-ray diffraction (XRD), Thermogravimetric Analysis (TGA), UL 94 Testing, Cone Calorimeter testing, image fracture observation, and Scanning Electron Microscope (SEM) were conducted on the OPT flame retardant composite board.